Analysis of Regional Revenue of Palu City for the 2019-2023 Period - Diki Diki; Musdayati Musdayati; Edhi Taqwa; Andi Herman Jaya; Nuryana Haprin; Mmaduabuchi Onwunyi Ugochukwu; Oghenekparobo Ernest Agbogun (Transpublika Publisher, 2025)
Indonesia's regional autonomy policies aim to enhance local fiscal independence, yet most regions, including Palu City, remain heavily dependent on central government transfers. This study analyzes the Local Revenue (Pendapatan Asli Daerah/PAD) of Palu City from 2019 to 2023. The research aims to understand the growth dynamics, contribution, elasticity, and effectiveness of PAD, particularly in the aftermath of the 2018 natural disasters and the Covid-19 pandemic. A quantitative approach was employed using formulas for growth, contribution, elasticity, and effectiveness to analyze secondary data on PAD components. The analysis focused on evaluating fiscal performance and resilience. PAD growth during 2019–2022 showed fluctuations, influenced by the 2018 earthquake, tsunami, and liquefaction, as well as the Covid-19 outbreak in 2021. These events led to decreased tax and retribution contributions and impacted other legitimate revenues. Elasticity analysis revealed that PAD is elastic which indicating that changes in revenue components significantly affect overall local revenue. Budget effectiveness analysis showed that PAD realization consistently met or exceeded targets. The findings highlight the need for diversification of revenue sources to enhance fiscal resilience. High elasticity values suggest that local financial planning must be adaptive to economic and social changes. The Palu City Government is advised to optimize tax and levy collection, explore alternative revenue streams, and build partnerships with the private sector. In anticipation of future shocks, establishing fiscal risk mitigation strategies such as reserve funds are essential. Effective budget management should continue to be prioritized through efficient expenditure practices.